Evaluation of Rat Density and the Associated Factors in Leptospirosis Endemic Areas: The First Report on the Use of BI-Index - Akbar, Zainul; Ristiyanto, Ristiyanto; Dwi-Handayani, Farida; Sayono, Sayono (Universitas Airlangga, 2024)
Introduction: Leptospirosis is a health problem in tropical countries where rats serve as the reservoir of Leptospira contamination. Previous investigations implementing the Bi-index to assess rat density in Leptospirosis endemic areas are highly limited. This study aimed to use the Bi-index in monitoring rat density and the associated factors in urban Leptospirosis endemic areas. Methods: Four endemic areas in Semarang City were selected as the study sites based on Leptospirosis data in Puskesmas Gayamsari. Live traps were positioned in one case house and 39-49 neighboring houses in a 100m radius, on three consecutive days. Trapped rats were collected for species identification, morphometrics evaluation, and calculation of Bi-index and rat indices, while environmental parameters were obtained through observation. Results and Discussion: 67.1% of participants were women, private employees, and aged 17-55, while trap success ranged from 2.5-26.5% with the Bi, diversity, dominance, and evenness indices of 0.02-0.32, 0.94-1.09, 0.36-0.44, and 0.79-0.96, respectively. Trapped species included Rattus norvegicus, Rattus tanezumi, and Mus musculus with proportions of 61.3%, 34.1%, and 4.7%, respectively. The presence of rats was associated with closeness to the river containing stagnant water, frequent flooding, water entering houses during floods, open trash bins, and rubbish bins around the houses. The high rat density, dominant species, and correlated environmental conditions are strategic targets in controlling Leptospirosis in Semarang City. Conclusion: The rat density (dominated by R. norvegicus) in Semarang City was correlated with water drainage and garbage management, hence further investigation was recommended to determine Leptospira bacterial infection in rodents.